The drosophila Bcl-2 family protein Debcl is targeted to the proteasome by the ?-TrCP homologue slimb. - Colin, J.; Garibal, J.; Clavier, A.; Rincheval-Arnold, A.; Gaumer, S.; Mignotte, B.; Guénal, I. (Apoptosis. An international journal on programmed cell death., 2014)
The ubiquitin-proteasome system is one of the main proteolytic pathways. It inhibits apoptosis by degrading pro-apoptotic regulators, such as caspases or the tumor suppressor p53. However, it also stimulates cell death by degrading pro-survival regulators, including IAPs. In Drosophila, the control of apoptosis by Bcl-2 family members is poorly documented. Using a genetic modifier screen designed to identify regulators of mammalian bax-induced apoptosis in Drosophila, we identified the ubiquitin activating enzyme Uba1 as a suppressor of bax-induced cell death. We then demonstrated that Uba1 also regulates apoptosis induced by Debcl, the only counterpart of Bax in Drosophila. Furthermore, we show that these apoptotic processes involve the same multimeric E3 ligase-an SCF complex consisting of three common subunits and a substrate-recognition variable subunit identified in these processes as the Slimb F-box protein. Thus, Drosophila Slimb, the homologue of ?-TrCP targets Bax and Debcl to the proteasome. These new results shed light on a new aspect of the regulation of apoptosis in fruitfly that identifies the first regulation of a Drosophila member of the Bcl-2 family.